Pengaruh Kinerja Lingkungan Dan Leverage Terhadap Pengungkapan Corporate Social Responsibility Pada Perusahaan Sektor Pertambangan, Kimia Dan Pertanian Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2016 - Hadi Swantara (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The aim of this research was to examine the effect of environmental performance Leverage and Profitability toward corporate social responsibility (CSR) disclosure of mines, chemical and farm company. The environmental performance was measured by the company performance in PROPER. This research attampts to used tree corporate characteristic, they are company Environmental Performance,Leverage and Profitability. Dependent variable used in this research was CSR disclosure. The population of this research is all the Mine,Chemical and Farm company listed in Indonesia Stock Exchange during 2014-2016. The total sample of this research was 96 companies. The collection of research data used purposive sampling method. The data analysis method used is analysis regression.The result showed that environmental performance and Leverage significantly influence to Corporate Social Responsibility Disclosure.